2018
DOI: 10.1111/bjhp.12297
|View full text |Cite
|
Sign up to set email alerts
|

Education‐based disparities in knowledge of novel health risks: The case of knowledge gaps in HIV risk perceptions

Abstract: We found support for the knowledge gap hypothesis. Over time, populations with greater education gained more knowledge about their HIV risk than populations with lower education. Results highlight the need to carefully consider health communication strategies to reach and address those individuals with low education and health knowledge. Statement of contribution What is already known on this subject? A meaningful potion of the population answers 'don't know' when asked to report their risk for health problems… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
25
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 30 publications
2
25
1
3
Order By: Relevance
“…They found a significant influence of both attitude and epidemic knowledge on the on-farm adoption of biosecurity practices by farmers. Moreover, this is also argued that knowledge gaps in health risks play an essential role in the prevention of AIDS ( Kiviniemi et al, 2018 ). In light of this, epidemic knowledge may play an integral role in shaping the epidemic prevention behaviors of individuals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found a significant influence of both attitude and epidemic knowledge on the on-farm adoption of biosecurity practices by farmers. Moreover, this is also argued that knowledge gaps in health risks play an essential role in the prevention of AIDS ( Kiviniemi et al, 2018 ). In light of this, epidemic knowledge may play an integral role in shaping the epidemic prevention behaviors of individuals.…”
Section: Discussionmentioning
confidence: 99%
“…The second group of researches was based on surveys and their interpretation through the response rate of certain variables on epidemic prevention ( Baghbanzadeh et al, 2020 ; Sued et al, 2016 ). The third group of the studies was based on the situation analysis of the disease profiles in terms of explaining their prevention and control measures ( Elmahdawy et al, 2017 ; Kiviniemi et al, 2018 ; Raude et al, 2019 ). Finally, the fourth group of studies focussed the epidemics like SARS-CoV of 2002, MERS-CoV of 2012, and COVID-19 ( Lai et al, 2020 ; Nishiura et al, 2020 ; You et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although we did not directly measure health literacy in our study, limited knowledge of cervical cancer and HPV may have contributed to the high proportion of women who did not know if they perceived themselves at risk (Kim & Han, 2016; Kiviniemi, Orom, Waters, McKillip, & Hay, 2018; Morris et al, 2013). Health literacy has been associated with increased knowledge of cancer and screening participation (Kim & Han, 2016; Lindau et al, 2002), but the relationship between perceived susceptibility and health literacy is not as clear (Kim & Han, 2016; Morris et al, 2013; Peterson, Dwyer, Mulvaney, Dietrich, & Rothman, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In its original formulation, the hypothesis posits that, compared to those with lower socioeconomic status (SES), individuals with higher SES should have more access to and use of health information and thus will be more likely to benefit from new health information . Over time this creates a gap in health knowledge between those with higher and lower SES that contributes to health disparities . Research has shown that rural residents have lower SES than urban residents, and thus they may have limited access to and use of health information due to the differential access posited by the knowledge gap hypothesis.…”
mentioning
confidence: 99%
“…15 Over time this creates a gap in health knowledge between those with higher and lower SES 15,16 that contributes to health disparities. 17 Research has shown that rural residents have lower SES than urban residents, 7 and thus they may have limited access to and use of health information due to the differential access posited by the knowledge gap hypothesis.…”
mentioning
confidence: 99%